2016
DOI: 10.1016/j.fuel.2015.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high oleic palm oil-based trimethylolpropane esters in a vacuum operated pulsed loop reactor

Abstract: The experimental studies have shown that a pulsed loop reactor can be used to successfully reduce the reaction time for the transesterification of oils and fats. In the present study, the transesterification of palm methyl ester (PME) and trimethylolpropane (TMP) to produce palm oil based TMP ester was conducted using the vacuum operated pulsed loop reactor. The reaction was catalyzed with sodium methoxide solution in methanol. The influences of five operating variables such as vacuum pressure, catalyst loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…The results indicated that all three base catalysts achieved high conversion (95.4 ± 1.80%) in 1.5 h one‐pot reactions. The results of using K 2 CO 3 and KOH are comparable to similar studies that utilized NaOMe as the catalyst . In earlier studies of methoxide catalysts, the overall reaction reached completion (>98%) in 1 h under the optimum conditions .…”
Section: Resultssupporting
confidence: 77%
“…The results indicated that all three base catalysts achieved high conversion (95.4 ± 1.80%) in 1.5 h one‐pot reactions. The results of using K 2 CO 3 and KOH are comparable to similar studies that utilized NaOMe as the catalyst . In earlier studies of methoxide catalysts, the overall reaction reached completion (>98%) in 1 h under the optimum conditions .…”
Section: Resultssupporting
confidence: 77%
“…As a result, mass transfer and consequently reaction yield increase. These observations are similar to those made by [31] who also found that the reaction yield increased with increasing oscillation frequency at a reaction temperature of 130 °C. However, they also showed that excessive values of oscillation frequency caused a reduction in the reaction yield.…”
Section: Oscillation Frequencysupporting
confidence: 91%
“…Hamidah et al [31], the effect of FAME to TMP molar ratio (ranging from 3.5:1 to 4.3:1) on palm oil based TFATE was investigated. Their results showed that the FAME to TMP molar ratio had influence on TFATE reaction yield over the chosen range.…”
Section: Fame To Tmp Molar Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The yield of the product does not usually exceed 95% and the crude ester require careful purifi cation. Fatty acid esters of TMP can be also obtained by transesterifi cation of fatty acid methyl esters (FAME) using conventional homogeneous basic catalyst [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%